Repo Runs - Martin, Antoine; Skeie, David; Thadden, Ernst-Ludwig von (Review of Financial Studies, 2014)
The recent financial crisis has shown that short-term collateralized borrowing may be a highly unstable source of funds in times of stress. In this paper, we develop a dynamic equilibrium model and analyze under what conditions such instability can be a consequence of market-wide changes in expectations. We derive a liquidity constraint and a collateral constraint that determine whether such expectations-driven runs are possible and show that they depend crucially on the microstructure of particular funding markets that we examine in detail. This provides insights into the differences between the tri-party repo market and the bilateral repo market, which were both at the heart of the recent financial crisis.